1998
DOI: 10.3758/bf03206041
|View full text |Cite
|
Sign up to set email alerts
|

Apparent body tilt and postural aftereffect

Abstract: Apparent orientation of the body tilted laterally in the frontal plane was studied with the methods of absolute judgments in four experiments. In Experiment 1, 17 subjects, who maintained the normal adaptation of body to gravity,estimated their body tilts under the condition of seeing the gravitational vertical and under the condition of eliminating it. The results showed that (1) there was not a significant difference between the two conditions and (2) the small tilts of less than 45°were exactly estimated, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 59 publications
4
18
0
Order By: Relevance
“…These results indicate that when judgments of body orientation are made, adding visual information may actually reduce the extent of the overestimations of body tilt. Similar findings by Higashiyama and Koga (1998) support the view that the distribution of atmospheric pressure on skin provides another cue to body tilt perception. Both studies showed no significant difference in estimated body tilt between participants whose eyes were open and those whose eyes were closed, although the average overall tilt overestimation was somewhat lower with eyes open.…”
Section: Multisensory Judgments Of Body Tiltsupporting
confidence: 78%
See 3 more Smart Citations
“…These results indicate that when judgments of body orientation are made, adding visual information may actually reduce the extent of the overestimations of body tilt. Similar findings by Higashiyama and Koga (1998) support the view that the distribution of atmospheric pressure on skin provides another cue to body tilt perception. Both studies showed no significant difference in estimated body tilt between participants whose eyes were open and those whose eyes were closed, although the average overall tilt overestimation was somewhat lower with eyes open.…”
Section: Multisensory Judgments Of Body Tiltsupporting
confidence: 78%
“…Models such as those of Perrone (1982) or Proffitt (Proffitt et al, 2001;Stefanucci et al, 2005) help explain the occurrence of slant overestimation as a visual illusion; yet other work supports the view that additional, nonvisual factors can also contribute to the perceived slant distortion, particularly when judgments involve multisensory information such as occurs with body tilt (Aksamit & Husak, 1983;Higashiyama & Koga, 1998;Ito & Gresty, 1997).…”
Section: Gender Differencesmentioning
confidence: 91%
See 2 more Smart Citations
“…Regarding the estimation of body tilt, results are quite inconsistent. Higashiyama and Koga (1998) recorded some fairly accurate estimates up to a 45º roll tilt. At higher roll tilts, the values were overestimated.…”
mentioning
confidence: 99%